Early School Exposure, Test Scores, and Noncognitive Outcomes - Thomas Cornelissen; Christian Dustmann (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
We estimate the effects of receiving additional schooling before age 5 on cognitive and noncognitive outcomes, exploiting unique school entry rules in England that cause variation in the age at school entry and the effective length of the first school year, and combining survey data with administrative school records up to 6 years after exposure. We find significant effects on both cognitive and noncognitive outcomes at ages 5 and 7, particularly so for boys with a disadvantaged parental background. At age 11, effects on cognitive outcomes have disappeared, while there is still evidence for effects on noncognitive outcomes.
Keywords: J13; I26; 330; Returns to early schooling; school entry age; child development